Carbohydr Polym Special Issue Invited contribution: Click chemistry for block polysaccharides with dihydrazide and dioxyamine linkers - A review. (15th February 2022) - Solberg, Amalie; Mo, Ingrid V.; Omtvedt, Line Aa.; Strand, Berit L.; Aachmann, Finn L.; Schatz, Christophe; Christensen, Bjørn E.
Abstract: Engineered block polysaccharides is a relatively new class of biomacromolecules consisting of chemical assembly of separate block structures at the chain termini. In contrast to conventional, laterally substituted polysaccharide derivatives, the block arrangement allows for much higher preservation of inherent chain properties such as biodegradability and stimuli-responsive self-assembly, while at the same time inducing new macromolecular properties. Abundant, carbon neutral, and even recalcitrant biomass is an excellent source of blocks, opening for numerous new uses of biomass for a wide range of novel biomaterials. Among a limited range of methodologies available for block conjugation, bifunctional linkers allowing for oxyamine and hydrazide 'click' reactions have recently proven useful additions to the repertoire. This article focuses the chemistry and kinetics of these reactions. It also presents some new data with the aim to provide useful protocols and methods for general use towards new block polysaccharides. Graphical abstract: Unlabelled Image